1948
DOI: 10.1021/ja01186a031
|View full text |Cite
|
Sign up to set email alerts
|

Alkaloids of Dichroa Febrifuga Lour.

Abstract: Alkaloids ok Dichroa febrífuga Lour. 2091The column was washed with water. In all, 30 ml. of eluate was collected and lyophilized.The solid product was triturated with boiling chloroform, and the chloroform solution filtered. Concentration of the filtrate to a small volume gave crystals which were filtered and washed with cold chloroform. The yield of crystalline product, m. p. 75-77°, was 35 mg. Recrystallization of the product from chloroform gave pure dihydrodesoxystreptose, m. p. 78-79°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
2

Year Published

1967
1967
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(28 citation statements)
references
References 0 publications
0
26
0
2
Order By: Relevance
“…The medical use of chang shan was described in an ancient Chinese pharmacopoeia (17) for the treatment of malaria and stomach cancer and as an expectorant, emetic, and febrifuge, with side effects of nausea and vomiting (10). Febrifugine was extracted (7) and was later identified as a quinazoline derivative with the molecular structure C 16 H 21 O 3 N 3 (15). The purified febrifugine displayed potent antimalarial activity and was 100 times as active as quinine against P. lophurae in duck models and 50 times as active as quinine against P. cynomolgi infection in rhesus monkeys (12,13).…”
mentioning
confidence: 99%
“…The medical use of chang shan was described in an ancient Chinese pharmacopoeia (17) for the treatment of malaria and stomach cancer and as an expectorant, emetic, and febrifuge, with side effects of nausea and vomiting (10). Febrifugine was extracted (7) and was later identified as a quinazoline derivative with the molecular structure C 16 H 21 O 3 N 3 (15). The purified febrifugine displayed potent antimalarial activity and was 100 times as active as quinine against P. lophurae in duck models and 50 times as active as quinine against P. cynomolgi infection in rhesus monkeys (12,13).…”
mentioning
confidence: 99%
“…The assay using febrifugine and isofebrifugine mixture from D. febrifuga roots also showed the activity in mice treated only at 1.0 mg/kg b.wt. It is reported that febrifugine showed approximately one hundred times the activity of quinine and isofebrifugine showed relatively slight activity against P. lophurae in ducks (Kuehl et al, 1948). It is possible that the properties or ratios of these alkaloids might be changed following fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…Otaksa belongs to the family Saxifragaceae which includes Dichroa febrifuga Lour. from the roots of which the quinazolone alkaloid febrifugine has been isolated as a malariacidal constituent (Koepfli et al, 1947;Kuehl et al, 1948;Koepfli et al, 1949), and thus it was suggested that the active alkaloid of H. macrophylla var. Otaksa leaf extract might have the same principle as that of D. febrifuga.…”
mentioning
confidence: 99%
“…Oshima and co-workers [28] reported the isolation and structural elucidation of two primary metabolites of febrifugine after its incubation for 1 hour at 37°C with mouse liver S9. Febrifugine is a highly potent anti-malarial alkaloid isolated from the roots, stem and leaves of the plant Dichroa febrifuga , a Chinese herb locally referred to as Chang Shan [29]. One of the major metabolites designated feb-A (Figure 1) showed extremely potent in vitro anti-plasmodial activity.…”
Section: Metabolism and Metabolite Identification Studiesmentioning
confidence: 99%